ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MAHASISWA UNTUK BERWIRAUSAHA (Studi Kasus Mahasiswa AgribisnisUIN Syarif Hidayatullah Jakarta) - Aditiya Yasmin; Mudatsir Najamuddin; Rizki Adi Puspita Sari (AGRIBUSINESS JOURNAL, 2018)
Entrepreneurship is the potential for development, both in number and quality of entrepreneurship itself. Indonesia faces the reality that the number of entrepreneurs is still small, at around 1,65% (Source: Berita Kementrian Koperasi dan Usaha Kecil dan Menengah, March 2015)), whereas it takes at least 2% of entrepreneurs to enable a prosperous country.This research was conducted by incorporating three factors that drive an action (Theory of Planned Behavior) which implemented as a supporting factor of entrepreneurship action; attitudes, subjective norms, and perceived behavioral control. The type of method used a quantitative analysis. Data was collected through questionnaires and documentation. Analysis technique used is multiple linear regression and using Likert scale for measurement. The population was a student of Agribusiness UIN Syarif Hidayatullah Jakarta from 2008, 2009, 2010,2011, and 2012. The sampling is using proportionate stratified random sampling. There are 80 respondents.This research has R square = 0,412. The results of the study showed: (1) attitudes, subjective norms, and perceived behavioral control is influencing simultaneously to encourage students for being an entrepreneur (p < 0,05) (2) There was a positive influence (partially) in each factors: attitude (p < 0,05), subjective norms (p < 0,05), and perceived behavioral control (p < 0,05) to affect students in entrepreneurship.